Price, Quality, and Promotion Synergize to Boost E-commerce Purchases in Indonesia: Dampak Ulasan Online, Harga, dan Pemasaran Viral terhadap Pembelian di Shopee - Maulana, Mohamad Danang; Hariasih, Misti (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the impact of price, product quality, and promotion on consumer purchasing decisions on Shopee, focusing on students from Muhammadiyah University Sidoarjo. Using a quantitative approach and data collected through questionnaires, the research employs multiple linear regression analysis via SPSS. Results indicate that price, product quality, and promotion each have a significant positive effect on purchasing decisions. Collectively, these variables also influence consumer behavior on Shopee. The findings suggest that competitive pricing, high product quality, and effective promotions are crucial for enhancing consumer purchasing decisions on e-commerce platforms. Highlight: Competitive pricing and high product quality positively affect consumer decisions on Shopee. Effective promotions significantly influence purchasing behavior among university students. Combined impact of price, quality, and promotions enhances consumer engagement on e-commerce platforms. Keywoard: Price, Product Quality, Promotion, Purchasing Decisions, E-commerce